2015
DOI: 10.1136/bcr-2015-211498
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous sternal fracture due to multiple myeloma requiring extensive surgical repair

Abstract: Spontaneous sternal fracture is a well-known complication of multiple myeloma due to osteolytic bone lesions. The possibility of a multiple myeloma should be thoroughly investigated in patients presenting with a spontaneous sternal fracture. This work up should go beyond protein electrophoresis alone as a monoclonal paraprotein is not always present. In some cases, the myeloma plasma cell clone produces only the free light chain (κ or λ) or may even be non-secretory. The underlying plasma cell dyscrasia is tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Again the past history of road side accident in the current case report is not a usual finding because the development of MM after the history of trauma has not been documented. Researchers and clinician has suggested that with the progression of MM the patient suffers multiple fractures due to lytic bone lesions 9,10 . In this case, the suspicion of MM was raised by MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…Again the past history of road side accident in the current case report is not a usual finding because the development of MM after the history of trauma has not been documented. Researchers and clinician has suggested that with the progression of MM the patient suffers multiple fractures due to lytic bone lesions 9,10 . In this case, the suspicion of MM was raised by MRI findings.…”
Section: Discussionmentioning
confidence: 99%